Medically tailored meals for the management of symptomatic ascites: the SALTYFOOD pilot randomized clinical trial. (12th November 2020) - Tapper, Elliot B; Baki, Jad; Nikirk, Samantha; Hummel, Scott; Asrani, Sumeet K; Lok, Anna S
Abstract: Background: Ascites is a costly, morbid complication of cirrhosis. Although a low-sodium diet is central to the clinical management of ascites, its efficacy is limited by poor adherence. We aimed to determine the feasibility and impact of low-sodium medically tailored meals (MTM) intervention. Methods: We enrolled 40 persons with cirrhosis and ascites at the time of a paracentesis in a 12-week, 1:1 randomized trial of standard of care (SOC) (low-sodium diet educational handout) or MTM with <2, 000 mg of sodium, >2, 100 kcal, and > 80 g of protein including a nocturnal protein supplement. We determined the proportion of eligible candidates recruited and adherence to MTM. The primary outcome was the number of paracenteses performed during weeks 0–12. We also collected ascites-specific quality-of-life (ASI-7) scores. Results: The median age of the enrolled subjects was 54 (IQR, 47–63) years, 46% were female, with median MELD-Na 18 (IQR, 11–23) and albumin 2.7 (IQR, 2.5–3.3) g/dL. At baseline, subjects reported a median of two (IQR, 1–3) paracenteses in the prior 4 weeks. Adherence to the meal schedule was excellent save for when hospitalizations occurred. After 12 weeks, patients in the MTM arm required fewer paracenteses per week than those in the SOC group [median (IQR): 0.34 (0.14–0.54) vs 0.45 (0.25–0.64)]. During the trial, four (20%) SOC patients died, whereas two (10%) died and one (5%) was transplanted in the MTM arm. Ascites-specific quality of life improved to a greater degree in the MTM arm compared to the SOC arm, by 25% (IQR, –11% to 61%) vs 13% (IQR, –28% to 54%). Conclusion: A trial of MTM for persons with ascites is feasible and potentially effective. Both arms experienced benefits, highlighting the role for improved education and closer monitoring in this challenging condition.